(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Iron deficiency anemia clinical manifestations appear that are explained the development of anemic hypoxia, which in turn increases the metabolic changes and trophic disorders present in the body. Updated criteria allow for early diagnosis and treatment before the development of damage to internal organs.